1984
DOI: 10.1093/geronj/39.5.583
|View full text |Cite
|
Sign up to set email alerts
|

Meaningfulness and Recall of Names by Young and Old Adults

Abstract: Names from one of four list conditions (elderly-relevant, young-relevant, nonmeaningful) were presented to 56 young and 56 old adults. Contrary to the findings often reported in the gerontological literature on memory, with free recall the elderly adults remembered as many names as did the young. Superior performance for the young was observed only in the young-relevant list condition. The elderly adults recalled significantly more names than did the young from the elderly- and both-relevant lists. No differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
6
0

Year Published

1990
1990
2007
2007

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…In agreement with these propositions, Hultsch and Dixon (1983) found that older subjects recalled more propositions from a text for which normative data indicated a high level of knowledge for older adults (a biographical sketch of Mary Pickford) compared to a text for which normative data indicated a low level of knowledge for older adults (a biographical sketch of Steve Martin). In addition, the results of that study showed exactly the opposite pattern of results for young subjects.This interaction between adult age and datedness of information has been found with other types of materials, such as single words (Barrett & Wright, 1981; Erber, Galt, & Botwinick, 1985; Worden & Sherman-Brown, 1983) and common names (Hanley-Dunn & Mcintosh, 1984). Thus, the importance of pertinent prior knowledge for the goodness of episodic remembering in old age is well documented.…”
mentioning
confidence: 70%
See 2 more Smart Citations
“…In agreement with these propositions, Hultsch and Dixon (1983) found that older subjects recalled more propositions from a text for which normative data indicated a high level of knowledge for older adults (a biographical sketch of Mary Pickford) compared to a text for which normative data indicated a low level of knowledge for older adults (a biographical sketch of Steve Martin). In addition, the results of that study showed exactly the opposite pattern of results for young subjects.This interaction between adult age and datedness of information has been found with other types of materials, such as single words (Barrett & Wright, 1981; Erber, Galt, & Botwinick, 1985; Worden & Sherman-Brown, 1983) and common names (Hanley-Dunn & Mcintosh, 1984). Thus, the importance of pertinent prior knowledge for the goodness of episodic remembering in old age is well documented.…”
mentioning
confidence: 70%
“…This interaction between adult age and datedness of information has been found with other types of materials, such as single words (Barrett & Wright, 1981; Erber, Galt, & Botwinick, 1985; Worden & Sherman-Brown, 1983) and common names (Hanley-Dunn & Mcintosh, 1984). Thus, the importance of pertinent prior knowledge for the goodness of episodic remembering in old age is well documented.…”
mentioning
confidence: 70%
See 1 more Smart Citation
“…Consequently, older adults are expected to show better episodic memory performance for dated information, whereas young adults should exhibit better performance for contemporary information. Indeed, such an interactive pattern between the age of the rememberer and the datedness of information has been reported for a variety of materials and testing conditions (Backman, 1991;Backman, Herlitz, & Karlsson, 1987;Barrett & Wright, 1981;Erber, Gait, & Botwinick, 1985;Hanley-Dunn & Mclntosh, 1984;Hultsch & Dixon, 1983;Worden & Sherman-Brown, 1983). Thus, for both young and older adults, the importance of pertinent prior knowledge for the level of episodic memory performance is well documented.…”
mentioning
confidence: 88%
“…);memorise meaningless syllables (Macht and Buschke, 1983); andrecognise unfamiliar faces (Ferris et al , 1980). However, once the experiments deal with realistic and meaningful information, no deficits of older subjects are found any more (Craik, 1968; Raymond, 1971; Hultsch, 1977; Capon and Kuhn, 1979; Wright, 1982; Hanley‐Dunn and McIntosh, 1984). Furthermore, older subjects tend to re‐interpret experimental settings in a way that they transfer meaning (Roberts et al , 1982).…”
Section: Two Conceptions Of the Age/performance Relationshipmentioning
confidence: 99%